2021
DOI: 10.1001/jamaoncol.2021.4932
|View full text |Cite
|
Sign up to set email alerts
|

Update of Incidence, Prevalence, Survival, and Initial Treatment in Patients With Non–Small Cell Lung Cancer in the US

Abstract: IMPORTANCE Updated estimates of non-small cell lung cancer (NSCLC) in the US are needed. OBJECTIVE To calculate the most recent epidemiologic estimates of NSCLC in the US. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional epidemiological analysis used the most recently released data from US cancer registries. The population-based US Cancer Statistics (USCS) database (2010-2017), comprised of the Surveillance, Epidemiology, and End Results (SEER) program and the National Program of Cancer Registries (NPCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
217
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(229 citation statements)
references
References 21 publications
8
217
0
4
Order By: Relevance
“…Of note, two previous studies using the SEER Program database have reported that recent increases in the incidence of stage I NSCLC diagnosed contributed to improvements in lung cancer survival. 20 21 These studies similarly suggested that these trends may be explained, in part, by increases in the early detection of lung cancer through screening. Our analysis differed from these studies in that we focused on evaluating patients aged 55-80 (patients potentially eligible for screening on the basis of age) and we used the NCDB to evaluate whether the rate of increase in stage I disease was significantly greater after the USPSTF recommended screening than it was before.…”
Section: Discussionmentioning
confidence: 92%
“…Of note, two previous studies using the SEER Program database have reported that recent increases in the incidence of stage I NSCLC diagnosed contributed to improvements in lung cancer survival. 20 21 These studies similarly suggested that these trends may be explained, in part, by increases in the early detection of lung cancer through screening. Our analysis differed from these studies in that we focused on evaluating patients aged 55-80 (patients potentially eligible for screening on the basis of age) and we used the NCDB to evaluate whether the rate of increase in stage I disease was significantly greater after the USPSTF recommended screening than it was before.…”
Section: Discussionmentioning
confidence: 92%
“…Lung cancer is the leading cause of cancer death worldwide and is commonly diagnosed in older patients, with the median age of diagnosis in the UK being 71 years (IQR 62-75). 1 Treatment rates, both curative and palliative in intent, decrease with age, 2 the reasons for which are complex and might include complications in treatment delivery due to comorbidities, poor functional status, and frailty, which are common in older people. These problems might be more marked in squamous-cell lung cancer, which accounts for 25% of cases of non-small-cell lung cancer (NSCLC), as this type of lung cancer commonly arises in patients who are currently or have previously been smokers and might be associated with smoking-related diseases such as chronic obstructive pulmonary disease, ischaemic heart disease, and peripheral vascular disease.…”
Section: Is It Time To Move On To the Next Generation Of Clinical Trials In Older Patients With Cancer?mentioning
confidence: 99%
“…Lung cancer is one of the most common malignancies worldwide, and approximately one-third of cases of nonsmall cell lung cancer (NSCLC) are locally advanced at the time of diagnosis (1). Platinum-based chemotherapy is routinely used to treat advanced or metastatic NSCLC.…”
Section: Introductionmentioning
confidence: 99%